Effects of indoor exposure to low level toluene on neural network alterations during working memory encoding. (April 2023) - Pan, Liping; Liu, Jie; Zhan, Changqing; Zhang, Xin; Cui, Mingrui; Su, Xiao; Wang, Zukun; Zhao, Lei; Liu, Junjie; Song, Yijun
Abstract: Objective: While high concentrations of toluene are known to affect multiple human organ systems, research concerning the influence of immediate, short-term exposure to toluene indoors and at low concentrations is scarce. Here, we studied effects of indoor toluene exposure on neural network alterations during working memory (WM) encoding. Methods: A total of 23 healthy college students were recruited. All participants were situated in a closed environmental chamber with a full fresh air system. Each participant was subjected to four exposure experiments with different toluene concentrations (0, 17.5, 35, and 70 ppb, named Group A, B, C and D, respectively), with at least one week between each experiment. WM Behavioral and 19-channel electroencephalogram (EEG) recordings in a pre-set environmental chamber were conducted simultaneously during each toluene exposure experiment. Neural networks relevant to WM encoding were visualized analyzing the obtained data. Results: 1. No significant difference in WM behavioral performance among the four groups was found. However, a significant increase in whole brain neural network functional connectivity was noted, especially in the frontal region. 2. An outflow directional transfer function (DTFoutflow ) revealed higher frontal region values among Group D (the 70 ppb group) as compared to Group A, B and C (the0, 17.5 ppb and 35 ppb groups, respectively), although no differences in frontal region DTFinflow values among the four groups were noted. 3. The DTFFZ-F7, DTFFZ-T5, DTFFZ-P4, DTFFZ-P3, DTFFP2-O2, DTFP3-T4, DTFP3-F4, DTFP4-CZ and DTFP4-T4 values of Group D were found to be higher as compared to those of Group A and B. Furthermore, DTFFZ-F7 and DTFP4-T4 values of Group C were higher as compared to those of Group A. The DTFFZ-F7 values of Group D were higher as compared to those of the Group C. Conclusion: Short-term toluene exposure significantly influences neural networks during cognitive processes such as WM encoding, even at low concentration. Graphical abstract: Image 1 Highlights: Short-term exposure to low concentrations of toluene to simulate indoor toluene exposure. EEG recordings were performed during a working memory task. Short-term toluene exposure significantly influences neural networks during WM encoding, even at low concentration.